About Stability of Solutions to Systems of Differential Equations (Global Journal of Science Frontier Research, 2024)
The stability conditions for solutions of systems of ordinary differential equations are considered The conditions and criteria for the use of partial and external derivatives are proposed This allows us to investigate the behavior of a function of several variables without requiring its differentiability but using only information on partial derivatives This reduces the restrictions on the degree of smoothness of the studied functions The use of the apparatus of external derived numbers makes it possible to reduce the restrictions on the degree of smoothness of manifolds when studying the question of the integrability of the field of hyperplanes Using the apparatus of partial and external derived numbers it can be shown that the investigation of the stability of solutions of a system of differential equations can be reduced to an investigation of the solvability of a system of equations of a special form
Keywords: solutions of differential equations; stability conditions; apparatus of partial and external derived numbers